2008
DOI: 10.1614/ws-08-073.1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Persistent Seed Banks of Invasive Plants by Soil Solarization—The Case of Acacia saligna

Abstract: An important factor in controlling invasive plant infestations is frequently the acceleration of the deterioration of their persistent seed bank, which is often associated with physical dormancy mechanisms. We hypothesized that breaking dormancy by heat would enhance the vulnerability of the nondormant seeds to hydrothermal stresses. The aim of the present study was to examine the effect of soil solarization treatments (heating the soil by means of polyethylene mulching) on buried Australian Acacia seeds, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…(2003); 2: Burrows et al. (2009); 3: Cohen et al. (2008); 4: Fourie (2008); 5: Grice & Westoby (1987); 6: C. Harris et al.…”
Section: Literature Review: Reproductive Biology Of Australian Acaciasmentioning
confidence: 99%
“…(2003); 2: Burrows et al. (2009); 3: Cohen et al. (2008); 4: Fourie (2008); 5: Grice & Westoby (1987); 6: C. Harris et al.…”
Section: Literature Review: Reproductive Biology Of Australian Acaciasmentioning
confidence: 99%
“…Using transparent polyethylene sheets, the temperature of the soil at a depth of 0–20 cm usually reaches 40–60 °C, leading to the eradication of pathogens, arthropod pests, and weeds. In an experiment conducted at an experimental agricultural farm, Cohen et al . demonstrated that soil solarization significantly reduced the viability of buried Acacia seeds, including A. saligna , A. murrayana F.Muell.…”
Section: Introductionmentioning
confidence: 99%
“…Richardson and Kluge suggested that soil solarization might be suitable for controlling the seed bank of Australian Acacia species in ‘sensitive habitats’. The effective control of A. saligna seed banks by soil solarization is attributed to a direct effect on dormancy release, which exposes non‐dormant seeds to the lethal hydrothermal conditions occurring during solarization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand‐pulling before establishment of the seeds has been shown to be effective in depleting the seed bank of small patches of invasives along roadsides or hiking trails (Concilio ) or in isolated nature reserve (Ruffino et al ), but requires annual treatments for at least 3 years and becomes impractical over large areas (Concilio ). Soil solarization, which consists in heating the soil by mulching it with plastic sheeting to inhibit seed viability (Cohen et al ), has certain limitations, such as length of treatment (i.e. several months), sunlight dependency, and variable effectiveness (Cohen & Rubin ).…”
Section: Introductionmentioning
confidence: 99%